Environmental determinants affecting the occurrence of defoliator caterpillars on Eucalyptus (Myrtaceae) plantations in the Brazilian Amazonian region - Zanuncio, Jose C.; Cruz, Adalton P.; Ramalho, Francisco S.; Serrao, Jose E.; Wilcken, Carlos F. [UNESP]; Silva, Wiane M.; Santos Junior, Valdeir C.; Ferreira-Filho, Pedro J. (Florida Entomological Soc, 2018)
Lepidoptera defoliators can be very damaging to eucalyptus plantations in Brazil. The objective of this study was to evaluate how plant age, the number of rotations, the tree growth rate (m' of wood per ha per yr), the distance of native vegetation strips from the eucalyptus plantations, and the width of these strips affect the population dynamics of Lepidoptera defoliators in eucalyptus crops. The survey of the lepidopteran species was conducted fortnightly from Sep 1992 to Aug 1994 using light traps in Eucalyptus urophylla S. T. Blake (Myrtaceae) plantations in 4 areas of the Brazilian Amazon region. In total, 1,049, 1,096, 1,020, and 853 Lepidoptera species with 4,413, 3,457, 3,226, and 2,222 individuals and 11, 11, 11, and 10 species of primary pests were recorded. The primary pest species were represented by 272, 772, 963, and 411 individuals, corresponding to 1.1, 1.0, 1.1, and 1.2% of the species and of 6.2, 22.3, 29.8, and 18.5% of the individuals collected in the 4 areas, respectively. Eupseudosoma aberrans Schaus (Arctiidae), Eupseudosoma involuta Sepp (Arctiidae), Nystalea nyseus Cramer (Notodontidae), Oxydia vesulia Cramer (Geometridae), Stenakidia grosica Schaus (Geometridae), and Thyrinteina arnobia Stoll (Geometridae) were the most abundant and represent 83.2% of primary pests species. The number of individuals of the primary pest species were not correlated with plant age, the number of rotations, the distance of native vegetation strips from the eucalyptus plantations, and the width these strips, but the total number of individuals of defoliating Lepidoptera had an inverse correlation with the growth rate (m' of wood per ha per yr) of eucalyptus plants.
Keywords: biological control; eucalypt; forest pest; light trap; monitoring; population dynamics